ANALISIS KETERSEDIAAN PANGAN POKOK DAN KONSUMSI ENERGI RUMAH TANGGA PETANI DI DESA TUKSONO KECAMATAN SENTOLO KABUPATEN KULON PROGO - Erlin Ratna Ambarsari; Nanik Dara Senjawati; Ni Made Suyastiri YP (Jurnal Dinamika Sosial Ekonomi, 2018)
The aim of this study are : (1) to analyze the level of staple food rice availability (2) to analyze energy consumption (3) to analyze the influence of income, the number of family's member and education on energy consumption (4) to identify the level of farmer's household food security. The research method of this study is descriptive analytical. To select research location, researches do purposively; these locations are Tuksono Village Sub district of Sentolo and District of Kulon Progo. To take sample of farmer, this research uses observation, interview, sampling method with 96 respondents being uses. This research uses observation, interview, record-keeping, and Food Frequency Questionnaires (FFQ) for data collections. Data analysis uses One Sample t-test and Multiple Linear Regression. The results are (1) the average of staple food rice availability in farmer's household by 1.814,95 kcal/capita/day is in the high category (2) the total energy consumption in farmer's household is 2.118,84 kcal/capita/day (3) the income, the number of family's member, and the education have an impact on energy consumption (4) the average of level of farmer's household food security in Tuksono Village is in the susceptible food categoryKeywords: Staple Food Availability, Energy Consumption, Income, the Number of Family's Member, Food Security